Giovani e pratiche di cittadinanza. Un’esperienza milanese - Gambardella, Maria Grazia (SocietàMutamentoPolitica, 2016)
Reporting the results of an empirical survey carried out with qualitative methods and referring to the Territorial Plan for Youth (2013-2014) implemented by the City of Milan to promote citizenship and participation, the article focuses on some new citizenship practices of young people in Milan, the ways and forms through which they reconstruct belonging, participation (political and social), and the public sphere. Citizenship at the same time, shows how the municipal institution, supported by the third and fourth sectors, can positively answer the questions of youth citizenship, recognizing young people as legitimate interlocutors to express their interests and needs.